2017
DOI: 10.1186/s13104-017-2552-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing regional models of congenital bleeding disorders: preliminary steps in the Italian context

Abstract: BackgroundAmong these diseases, congenital bleeding disorders (CBD) represent a significant societal burden in terms of high morbidity costs and health outcomes. In Italy, the organization and provision of health care is a regional responsibility and regions must assure equity and quality to all their residents. This is also true for CBD care which is provided by 54 multidisciplinary Hemophilia Treatment Centers (HTCs) distributed among the regions. With the present study, we intend to stimulate a debate on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…National networks were established in some larger MS and provide basis for RD care pathways [Plan National Maladies Rares 2018-2022. Interregional collaboration reduces regional inequities and provides means for care pathways and referrals to ERNs in regionalized healthcare systems [Nuti et al 2017;Harrison et al 2015]. Centralization of services through designation and accreditation of RD CoE and careful endorsement of applicants for ERN FM ensure saving of scarce resources and provision of high-quality services [Pasquali et al 2019;Peycelon et al 2017;Pakarinen et al 2017].…”
Section: Solutions and Opportunitiesmentioning
confidence: 99%
“…National networks were established in some larger MS and provide basis for RD care pathways [Plan National Maladies Rares 2018-2022. Interregional collaboration reduces regional inequities and provides means for care pathways and referrals to ERNs in regionalized healthcare systems [Nuti et al 2017;Harrison et al 2015]. Centralization of services through designation and accreditation of RD CoE and careful endorsement of applicants for ERN FM ensure saving of scarce resources and provision of high-quality services [Pasquali et al 2019;Peycelon et al 2017;Pakarinen et al 2017].…”
Section: Solutions and Opportunitiesmentioning
confidence: 99%
“…Accessibility to treatment is an understudied issue in the scientific literature, with territorial specificities, and in the diffusion of novel treatments 17 . Furthermore, accessibility is often analysed regarding access to care facility but a gap remains in the access to treatment, which is rarely investigated 18,19 . One of the learnings from a recent study, identified that travel time to care facilities (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…17 Furthermore, accessibility is often analysed regarding access to care facility but a gap remains in F I G U R E 2 Levels of satisfaction with treatment accessibility for persons with haemophilia and other coagulation deficiencies the access to treatment, which is rarely investigated. 18,19 One of the learnings from a recent study, identified that travel time to care facilities (i.e. 30-min access to the hospital pharmacy) was an insufficient parameter in the absence of a measure of perceived quality-of-life of the patients themselves.…”
Section: Strengths and Limitationsmentioning
confidence: 99%